PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V PADA MATERI PESAWAT SEDERHANA - Pratiwi, Cindi Oktaviani; Sujana, Atep; Jayadinata, Asep Kurnia (Jurnal Pena Ilmiah, 2017)
After initial observation of simple tool material gained a problem. Problems of the teacher is the lack of mastery of learning materials, while the problems of students are less participating students during the learning process. From these problems, applied inquiry model of learning. The purpose of this research is to know learning by using inquiry learning model. The method used is classroom action research, with research design of Kemmis and Taggart. The target that has been determined for student activity and the result of student learning completeness 85%, while for teacher performance 100%. Data obtained from the results of research, namely teacher performance in the cycle I 75%, cycle II 87.5% and 100% cycle III. The student activity cycle I 44%, 70% cycle and cycle III 87%. Student learning outcomes in cycle I 48%, cycle II 70% and cycle III 87%.Â